2020
DOI: 10.1093/nar/gkaa489
|View full text |Cite
|
Sign up to set email alerts
|

Pathological mutations in PNKP trigger defects in DNA single-strand break repair but not DNA double-strand break repair

Abstract: Abstract Hereditary mutations in polynucleotide kinase-phosphatase (PNKP) result in a spectrum of neurological pathologies ranging from neurodevelopmental dysfunction in microcephaly with early onset seizures (MCSZ) to neurodegeneration in ataxia oculomotor apraxia-4 (AOA4) and Charcot-Marie-Tooth disease (CMT2B2). Consistent with this, PNKP is implicated in the repair of both DNA single-strand breaks (SSBs) and DNA double-strand breaks (DSBs); lesions that can t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
44
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(51 citation statements)
references
References 57 publications
7
44
0
Order By: Relevance
“…In contrast, K137A mutant (Mean of column: 6.434) did not show statistically significant difference compared with FL PNKP (Mean of column: 6.302) and K142A mutant (Mean of column: 4.384) showed mild attenuation in nuclear localization ( Fig 3D ). In addition, to analyze DNA repair efficiency, we performed immunofluorescence experiments using γ-H2AX antibody as the DNA double-strand breaks marker or a PAN-ADP-ribose binding regent as the DNA single-strand breaks marker [ 39 41 ] after IR exposure in U2OS cells ( Fig 4A and 4B ). PNKP depletion by 3’-UTR siRNA PNKP caused delay in DSB repair as compared to siLUC control cells (γ-H2AX positive cells were 69.8% and 14.6%, respectively).…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, K137A mutant (Mean of column: 6.434) did not show statistically significant difference compared with FL PNKP (Mean of column: 6.302) and K142A mutant (Mean of column: 4.384) showed mild attenuation in nuclear localization ( Fig 3D ). In addition, to analyze DNA repair efficiency, we performed immunofluorescence experiments using γ-H2AX antibody as the DNA double-strand breaks marker or a PAN-ADP-ribose binding regent as the DNA single-strand breaks marker [ 39 41 ] after IR exposure in U2OS cells ( Fig 4A and 4B ). PNKP depletion by 3’-UTR siRNA PNKP caused delay in DSB repair as compared to siLUC control cells (γ-H2AX positive cells were 69.8% and 14.6%, respectively).…”
Section: Resultsmentioning
confidence: 99%
“…However, the removal was much less efficiently than WT cells, so the authors suggested an alternative 3'-phosphatase. In a recent work, only MCSZ cell lines exhibit a defect in repair of IRinduced SSBs implicating reduced PNKP-dependent DNA phosphatase [43]. The authors concluded that it is reduced DNA 5'-kinase activity that is the major contributor and/or cause of the neurodegeneration in PNKP-mutated disease.…”
Section: Mutational Survivorship Biasmentioning
confidence: 98%
“…This could explain recent findings suggesting that DSBR is not the cause of the neuropathology associated with PNKP-mutated diseases. In this experiment, authors only used patient-derived fibroblasts and were irradiated even at lower dose (2 Gy) [43].…”
Section: Mutational Survivorship Biasmentioning
confidence: 99%
“…However, the removal was much less efficiently than WT cells, so the authors suggested an alternative 3'-phosphatase. In a recent work, only MCSZ cell lines exhibit a defect in repair of IR-induced SSBs implicating reduced PNKP-dependent DNA phosphatase (Kalasova et al, 2020). The authors concluded that it is reduced DNA 5'-kinase activity that is the major contributor and/or cause of the neurodegeneration in PNKP-mutated disease.…”
Section: Mutational Survivorship Biasmentioning
confidence: 99%
“…This could explain recent findings suggesting that DSBR is not the cause of the neuropathology associated with PNKP-mutated diseases. In this experiment, authors only used patient-derived fibroblasts and were irradiated even at lower dose (2 Gy) (Kalasova et al, 2020). Another experiment using PNKP-deficient HCT116 and HeLa cells generated with CRISPR/Cas9 showed that cells were biochemically competent in removing both protruding and recessed 3'-phosphates from synthetic DSB substrates (Chalasani et al, 2018).…”
Section: Mutational Survivorship Biasmentioning
confidence: 99%